2018
DOI: 10.1039/c8ta02775g
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability and miscibility of co-evaporated methyl ammonium lead halide (MAPbX3, X = I, Br, Cl) thin films analysed by in situ X-ray diffraction

Abstract: We present the identification of crystalline phases by in situ X-ray diffraction during growth and monitor the phase evolution during subsequent thermal treatment of CH3NH3PbX3 (X = I, Br, Cl) perovskite thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 56 publications
7
46
0
Order By: Relevance
“…The thin MAPb(I 1−x Br x ) 3 film diffractograms (Figures 2A,B) show the presence of all the prominent peaks of cubic MAPbBr 3 and the (001) peak corresponding to PbI 2, but do not contain the principal (110) peak characterizing tetragonal MAPbI 3 . This points to the fact that the tetragonal phase of MAPbI 3 is transformed to the cubic phase of MAPbBr 3 as MAPb(I 1−x Br x ) 3 is formed, consistent with previous reports (Noh et al, 2013;Gilescrig et al, 2015;Pistor and Burwig, 2018). The value of bromine mole ratio x was determined using an empirical relationship between the bandgaps of the MAPb(I 1−x Br x ) 3 alloy and those of its MAPbI 3 and MAPbBr 3 components, given in Equation 1,…”
Section: Device Characterizationsupporting
confidence: 91%
See 2 more Smart Citations
“…The thin MAPb(I 1−x Br x ) 3 film diffractograms (Figures 2A,B) show the presence of all the prominent peaks of cubic MAPbBr 3 and the (001) peak corresponding to PbI 2, but do not contain the principal (110) peak characterizing tetragonal MAPbI 3 . This points to the fact that the tetragonal phase of MAPbI 3 is transformed to the cubic phase of MAPbBr 3 as MAPb(I 1−x Br x ) 3 is formed, consistent with previous reports (Noh et al, 2013;Gilescrig et al, 2015;Pistor and Burwig, 2018). The value of bromine mole ratio x was determined using an empirical relationship between the bandgaps of the MAPb(I 1−x Br x ) 3 alloy and those of its MAPbI 3 and MAPbBr 3 components, given in Equation 1,…”
Section: Device Characterizationsupporting
confidence: 91%
“…Previous studies have shown that MAPb(I 1−x Br x ) 3 with such high amounts of x exists in the cubic phase (Noh et al, 2013;Zhang et al, 2016). Pistor and Burwig (2018) gave an elaborate explanation for the formation of MAPb(I 1−x Br x ) 3 by exposing MAPbI 3 to MABr vapor and MAPbBr 3 to MAI vapor. They proved that it was due to reversible halide exchange at high substrate temperatures and added that it is much easier to replace I with Br than to replaces Br with I.…”
Section: Structural Propertiesmentioning
confidence: 94%
See 1 more Smart Citation
“…32 Other characterization methods can be undertaken in situ, using bespoke deposition chambers to take measurements in real time, or ex situ, by growing films of increasing thickness under the same conditions. In situ X-ray diffraction (XRD) measurements have been carried out during co-evaporation of several metal halide perovskites, 49,50 however the time resolution is limited by the amplitude of the signal, and so these measurements were not able to capture the early stages of growth where the signal is low. Ex situ XRD 51 and XPS [51][52][53] measurements on MAPbI 3 show the formation of additional species at the perovskite-substrate interface such as PbI 2 51,53 and decomposition products of MAI, 52 which prevents the growth of pure MAPbI 3 thin films.…”
Section: Introductionmentioning
confidence: 99%
“…deposited perovskite films, 93,94 might be related with the porosity observed by SEM (Figure 2b), suggesting a limited connectivity and hence uncorrelated growth of the grains. It is interesting to point out that phasepure CsPbI2Br can be readily obtained through vacuum deposition, while it cannot be formed by mechanochemical synthesis even after thermal treatment at 650 ℃.…”
Section: -Sourcesmentioning
confidence: 96%